PENGARUH SIKAP MANDIRI, MOTIVASI, PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA (Studi kasus pada UMKM muda yang baru memulai usaha Di Kelurahan Kota Matsum II, Medan di bidang kuliner) - Sheilla dwiyanthi; Hafizah; Aulia Arief Nasution (CV. Tungga Esti, 2023)
This study aims to determine whether independent attitudes, motivation, entrepreneurial knowledge affect entrepreneurial interest, to determine whether independent attitudes affect entrepreneurial interest, to determine whether motivation affects entrepreneurial interest, to determine whether entrepreneurial knowledge affects entrepreneurial interest. In this study, the population consists of 1683 residents who live in Kota Matsum II Medan Urban Village. The sample taken was 115 people who were young UMKM entrepreneurs in Kota Matsum II Village. the analytical methods used include multiple linear regression, and in addition, tests such as data quality tests and classical assumption tests. The results showed that the independent attitude variable has a positive and significant effect on entrepreneurial interest. Motivation has a positive and significant effect on entrepreneurial interest. Entrepreneurial knowledge has a positive and significant effect on entrepreneurial interest in young UMKM who are just starting a business in Kota Matsum II Village, Medan in the culinary field.